Correlation of Students' Questioning Skills Profile and Critical Thinking Ability on Science Subject Using Inquiry Model - Suriyani Suriyani; Tri Santoso; Sitti Rahmawati (Jurnal Akademika Kimia, 2024)
This study aims to describe the profile of the questioning skills of grade 5 students of SDN Inpres I Lasoani in science subjects after the inquiry learning model was applied. Moreover, to describe the correlation between students' questioning skill profiles and critical thinking ability at the application and analysis levels. This research is a mixed method (Mixed Methods), which is a research approach that combines quantitative and qualitative forms. The population in this study was the 5th-grade students of SD Inpres I Lasoani, Mantikulure District, East Palu, totaling  41 students. The researcher used the purposive sampling technique to select the subjects; they are 12 students selected as a sample, with the level of science learning ability categorized into 3 groups: high, medium, and low. Data collection techniques are observation, posttest, and documentation. The data in this study are qualitative, consisting of percentages derived from observations. The students' questioning skills get a score of 43.33 and are included in the medium category. In contrast, critical thinking skills with inquiry learning were 62.71% at the medium N-gain level in the high cognitive group, and 50.11% at the medium N-gain level in the moderate cognitive group. The low cognitive group obtained 46.22% at the N level. -medium gain. Thus, the improvement in the critical thinking skills of SD 5 Lasoani students after participating in inquiry learning was in the medium category. There is a positive correlation between the ability to ask questions and critical thinking.